Meningkatkan Hasil Belajar IPS Dengan Menggunakan Alat Peraga Peta - Jannatun Jannatun (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This classroom action research aims to increase student's interest and learning outcomes on social studies subjects of natural and socio-cultural diversity of fourth grade students of SD Negeri 050757 Alur Dua Semester 1 academic year 2017/2018 using map props. The subjects were 20 students of grade IV of SD Negeri 050757 Alur Dua tahun lesson 2017/2018. Data analysis is conducted qualitatively and quantitatively at the end of the learning cycle of student learning result data, and data of observation result of student's learning interest. The result of data analysis of research result showed that the use of map props to increase student's learning interest and achievement in IPS learning create a conducive learning atmosphere. In the first cycle after the learning is done by applying the map props, the learning outcomes increase from the average value of 58 at the initial condition to 68 in the first cycle with a complete learning of 12 students (60%). In the second cycle by applying the learning tool the learning outcomes increased to an average of 71.50 with a 90% student completeness level. It can be concluded that the use of map props on the IPS lesson of natural appearance and socio-cultural diversity can increase learning process, interest and learning outcomes of fourth grade students of SD Negeri 050757 Alur Dua Semester 1 Year Lesson 2017/2018. Keywords: maps, props Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan minat dan hasil belajar siswa pada mata pelajaran IPS materi kenampakan alam dan keragaman sosial budaya siswa kelas IV SD Negeri 050757 Alur Dua Semester 1 Tahun Pelajaran 2017/2018 dengan menggunakan alat peraga peta. Subjek penelitian adalah 20 orang siswa kelas IV SD Negeri 050757 Alur Dua tahun pelajaran 2017/2018. Analisis data dilaksanakan secara kualitatif dan kuantitatif pada setiap akhir siklus pembelajaran terhadap data hasil belajar siswa, dan data hasil observasi minat belajar siswa. Hasil analisis data hasil penelitian menunjukkan bahwa penggunaan alat peraga peta untuk meningkatkan minat dan prestasi belajar siswa dalam pembelajaran IPS membuat suasana pembelajaran yang kondusif. Pada siklus pertama setelah pembelajaran dilakukan dengan menerapkan alat peraga peta, hasil belajar meningkat dari nilai rata-rata 58 pada kondisi awal menjadi 68 pada siklus pertama dengan ketuntasan belajar sebesar 12 siswa (60%). Pada siklus kedua dengan menerapkan alat peraga peta hasil belajar meningkat menjadi rata-rata 71,50 dengan tingkat ketuntasan belajar siswa sebesar 90%. Dapat disimpulkan penggunaan alat peraga peta pada pembelajaran IPS materi kenampakan alam dan keragaman sosial budaya dapat meningkatka proses pembelajaran, minat dan hasil belajar siswa kelas IV SD Negeri 050757 Alur Dua Semester 1 Tahun Pelajaran 2017/2018. Kata kunci: alat peraga, peta